2019
DOI: 10.1590/s1677-5538.ibju.2018.0774
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant action of alpha lipoic acid on the testis and epididymis of diabetic rats: morphological, sperm and immunohistochemical evaluation

Abstract: Introduction Chronic hyperglycemia is caused by diabetes mellitus-committed genital morphophysiology, and oxidative stress is one of the main factors involved in this process. Alpha lipoic acid (ALA) can prevent metabolic and morphological changes in diabetic individuals.Objectives In present study, we evaluated the effects of regular ALA consumption on the spermatogenesis and histoarchitecture in the male genital system of diabetic rats.Materials and Methods Thirty-two Wistar rats were divided into groups: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Notably, testis and epididymis are well known as androgen-dependent organs (Mäkelä et al, 2019). Moreover, in STZ-induced diabetic animals, studies indicated that low testosterone level is a relevant factor acting on the morphometrical alterations observed here, such as reduction in the tubular diameter, the epithelial height, and the number of Sertoli and germ cells that, in the end, influenced the diminished DSP (Kianifard et al, 2012; Korejo et al, 2016; Das et al, 2017; Corrêa et al, 2019; Souza et al, 2019). Altogether, these results confirmed the adverse effects of diabetes on the testis and epididymis of Wistar rats.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, testis and epididymis are well known as androgen-dependent organs (Mäkelä et al, 2019). Moreover, in STZ-induced diabetic animals, studies indicated that low testosterone level is a relevant factor acting on the morphometrical alterations observed here, such as reduction in the tubular diameter, the epithelial height, and the number of Sertoli and germ cells that, in the end, influenced the diminished DSP (Kianifard et al, 2012; Korejo et al, 2016; Das et al, 2017; Corrêa et al, 2019; Souza et al, 2019). Altogether, these results confirmed the adverse effects of diabetes on the testis and epididymis of Wistar rats.…”
Section: Discussionmentioning
confidence: 83%
“…Several relevant studies demonstrate that the use of antioxidants reduced the harmful oxidative effects of chronic hyperglycemia and preserved organs and tissues [17,39]. At the end of 8 weeks, a reduction in glycemia (not statistically signifi cant) was observed in the diabetic rats supplemented with ALA compared to the non-supplemented diabetic group.…”
Section: Discussionmentioning
confidence: 97%
“…ALA is especially promising in diabetic conditions due to its antioxidant action [15]. It acts as a regulator of glucose metabolism, increasing sensitivity to peripheral insulin and aiding glycemic control [16,17]. Unlike other antioxidants such as Vitamin C and Vitamin E, ALA has an amphipathic behavior [18], making it more effi cient.…”
Section: Introductionmentioning
confidence: 99%
“…The glycemic levels equal to or greater than 270 mg/ dL were satisfactory for diabetic induction (Mohasseb et al, 2011). Moreover, the serum glucose levels were quantified weekly until the end of the experiment (Corrêa et al, 2019). After 8 weeks of the establishment of diabetes, all animals (control and diabetic group) were euthanized with xylazine and ketamine.…”
Section: Methodsmentioning
confidence: 99%